Pengaruh Kepemilikan Asing dan Corporate Governance terhadap Firm Performance yang dimediasi oleh R&D Intensity pada Perusahaan Food and Beverages - Sri Wahyuni; Ronny Malavia Mardani; Nurhidayah Nurhidayah (Ekonomis: Journal of Economics and Business, 2026)
This study aims to analyze the effect of foreign ownership and corporate governance on firm performance, with R&D intensity as a mediating variable in food and beverage companies listed on the Indonesia Stock Exchange for the 2021–2024 period. This study uses a quantitative approach with secondary data obtained from annual reports and company financial statements, and analyzed using the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS). The results show that foreign ownership and corporate governance have a significant positive effect on R&D intensity. In addition, foreign ownership has a significant positive effect on firm performance, while corporate governance has no significant direct effect on firm performance. The results of the mediation test indicate that R&D intensity significantly mediates the relationship between foreign ownership and firm performance, but is unable to mediate the relationship between corporate governance and firm performance. This study concludes that R&D intensity acts as a strategic mechanism that strengthens the influence of foreign ownership on improving firm performance, thus providing an empirical contribution in explaining the role of innovation as a link between ownership structure and firm performance in the food and beverage industry listed on the Indonesia Stock Exchange for the 2021–2024 period.